Knowledge Transfer in Creative Industry Succession: A Case Comparison Study of Indonesian Architectural Design Firms - Nuradhi, Maureen; Kristanti, Lili; Nasruddin, Ellisha; Wibowo, Helen; Paulus; Fatimah, Row Aulia (Jurnal Aplikasi Manajemen, 2025)
Only around 4% of Indonesian architecture firms survive for more than one generation, according to data from the Indonesian Association of Consulting Firms. In contrast, these enterprises have a longer lifespan in the United States and Europe, where the figures are greater. Even after the founders' deaths, these companies' well-known brands are frequently maintained by their surviving family members or partners. This study aims to identify the types of knowledge that are passed down between generations in a firm whose primary activities are related to creativity and have been proven to span multiple generations. Furthermore, it seeks to understand how this transfer is managed. A qualitative approach was employed for this study. Interviews were conducted with representatives of three renowned architecture firms, an association that represents architecture firms, and members of the architectural community to collect and cross-verify the data. The architecture firm’s founder frequently advocates for the second generation's right to self-expression. Because of this, succession usually happens naturally as opposed to through a planned procedure. The results show that the types of knowledge in architectural firms consist of a combination of explicit and tacit knowledge, both in the form of knowledge related to firm management and knowledge related to design project management. The findings on the management process reveal two types, which are managed naturally in everyday experience, and those that are planned. Through routine activities, the knowledge and skills are transmitted. It is anticipated that the knowledge gained from this study will enhance the administration of the creative sector, particularly in architecture, which could lead to a higher number of successful architectural projects and support their growth.